1993
DOI: 10.1139/t93-011
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic conductivity and diffusion monitoring of the Keele Valley Landfill liner, Maple, Ontario

Abstract: The 99-ha Keele Valley Landfill is located in a former sand and gravel pit at Maple, Ontario. The base and sides of the pit are lined with a minimum of 1.2 m of excavated clayey silt till recompacted to achieve a design hydraulic conductivity of 1 × 10−8 cm/s or less. Extensive construction controls and monitoring programs have been implemented to determine the hydraulic conductivity and advective performance of the liner. A total of 267 postcompaction laboratory hydraulic conductivity (k) tests indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 5 publications
2
24
0
Order By: Relevance
“…The data appear to be log-normally distributed with standard deviation (log 10 ) of 0.1. The hydraulic conductivity is similar to that observed by King et al (1993) for the Keele Valley Landfill using a similar Halton Till and similar construction specifications. The liner had a degree of saturation (after compaction) of 86% or higher, and essentially all compaction data points (water content ω, dry density ρ d ) fell above the line of optimums.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The data appear to be log-normally distributed with standard deviation (log 10 ) of 0.1. The hydraulic conductivity is similar to that observed by King et al (1993) for the Keele Valley Landfill using a similar Halton Till and similar construction specifications. The liner had a degree of saturation (after compaction) of 86% or higher, and essentially all compaction data points (water content ω, dry density ρ d ) fell above the line of optimums.…”
Section: Discussionsupporting
confidence: 79%
“…For the cell 2 (west) liner, 26 hydraulic conductivity tests were performed (4.7 tests/ha) and these gave results very similar to those for cell 1, with a maximum value of 1.4 × 10 -8 cm/s, a geometric mean of 0.98 × 10 -8 cm/s, and a standard deviation (log 10 k) of 0.11. Thus, the quality of the cell 2 liner appears to be similar to that of cell 1 and the quality of the 15 ha of the liner constructed at the Halton Landfill between 1992 and 1998 appears to be similar to that obtained at the Keele Valley Landfill (King et al 1993).…”
Section: Recompacted Clayey Silt Till Linersupporting
confidence: 55%
“…A case study of the Keele Valley Landfill reported in King et al [41] has been considered. The Keele Valley Landfill at Maple, Ontario, approximately 10 km north of Metropolitan Toronto, is owned and operated by the Municipality of Metropolitan Toronto Department of Works.…”
Section: Case Study 2: Keele Valley Landfillmentioning
confidence: 99%
“…The migration of contaminants from solid waste landfills through both natural and compacted clay has been examined through several well documented case histories (Goodall and Quigley, 1977;Barone et al, 1991;King et al, 1993). In most cases, these low hydraulic conductivity natural clay deposits or compacted clay liners minimize the advective flux of contaminants through the clay resulting in diffusion becoming the dominant contaminant transport mechanism (for an exception, see Munro et al, 1997).…”
Section: Introductionmentioning
confidence: 99%